Mengembangkan Strategi Bisnis di Era Transformasi Digital - Dwi Robiul Rochmawati; Hani Hatimatunnisani; Mira Veranita (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
As contemporary organizations go through computerized change, the job of a practical methodology turns out to be vital for any organization. There are different significant perspectives to zero in on while fostering a computerized business system: specifically, expanding the extent of business tasks as well as carrying out the most recent IT answers for make this procedure a long haul